Macrophage Sphingosine 1-Phosphate Receptor 2 Blockade Attenuates Liver Inflammation and Fibrogenesis Triggered by NLRP3 Inflammasome - Hou, Lei; Yang, Le; Chang, Na; Zhao, Xinhao; Zhou, Xuan; Dong, Chengbin; Liu, Fuquan; Yang, Lin; Li, Liying (Frontiers in Immunology, 2020)
NLR family pyrin domain containing 3 (NLRP3) inflammasome accompanies chronic liver injury and is a critical mediator of inflammation-driven liver fibrosis. Sphingosine 1-phosphate (S1P)/S1P Receptor (S1PR) signaling participates in liver fibrogenesis by affecting bone marrow (BM)-derived monocytes/macrophages (BMMs) activation. However, the relationship between S1P/S1PRs signaling and NLRP3 inflammasome in BMMs remains unclear. Here, we found significantly elevated gene expression of NLRP3 inflammasome components (NLRP3, pro-interleukin-1β, and pro-interleukin-18) and the activation of NLRP3 inflammasome significantly elevated during murine chronic liver injury induced by bile duct ligated operation, methionine-choline-deficient and high-fat diet or carbon tetrachloride intraperitoneal injection. Moreover, the increased expression of sphingosine kinase 1 (SphK1), the rate-limiting synthetic enzyme of S1P, was positively correlated with NLRP3 inflammasome components in both patients and mouse model livers. Flow cytometry analysis and immunofluorescence staining showed BMMs contributed to the significant proportion of NLRP3+ cells in murine inflammatory livers, but not Kupffer cells, dendritic cells, endothelial cells, T cells and hepatocytes. Focusing on macrophages, S1P promoted NLRP3 inflammasome priming and activation in dose-dependent manner. Blockade of S1PR2 by JTE-013 (antagonist of S1PR2) or S1PR2-siRNA inhibited S1P-induced NLRP3 inflammasome priming and inflammatory cytokine (interleukin-1β and interleukin-18) secretion, whereas blockade of S1PR1 or S1PR3 had no such effect. In vivo, β1,3-d-glucan–encapsulated siRNA particles (GeRPs) delivery system is capable of silencing gene in macrophages specifically. Treatment with S1PR2 siRNA-GeRPs markedly reduced NLRP3 inflammasome priming and activation, and attenuated liver inflammation and fibrosis. Together, the conclusions indicated that targeting macrophage S1PR2 retarded liver inflammation and fibrogenesis via downregulating NLRP3 inflammasome, which may represent an effective therapeutic strategy for chronic liver injury.